Two-dimensional modeling of water distribution under capillary wick irrigation system - Kamal, Md. Rowshon; Muhammed, Hadi Hamaaziz; Mojid, Mohammad Abdul; Anlauf, Ruediger; Mohd Soom, Mohd Amin (Universiti Putra Malaysia Press, 2019)
Competition for limited available water for crop production is an ever-increasing issue for farmers due to increasing demand of irrigation water worldwide. Due to high energy cost in operating pressurized irrigation systems, energy-efficient low-pressure wick irrigation systems can play important roles for smallholder greenhouse crop production by ensuring higher water use efficiency than most traditional approaches. The objectives of this study were to investigate HYDRUS 2D-simulated water distribution patterns in soil and soilless growing media, and to evaluate water balance in these media under capillary wick irrigation system. To accomplish these objectives, eggplants (Solanum melongena L.) were grown in potted peatgro and sandy clay loam in a greenhouse experiment, water distribution was simulated by using HYDRUS 2D software package and compared with the measured values, and water uptake by the plant roots was determined for water balance calculation. The wetting pattern was found axially symmetric in both growing media (peatgro and soil) under the wick emitters. The simulated water distribution in both growing media revealed dependency of spatial extent of the wetted zone on water application period and hydraulic properties of the media. The mean absolute error (MAE) in water content over depth varied from 0.04 to 0.10 m3 m-3 and the root mean square error (RMSE) varied from 0.04 to 0.11 m3 m-3. Deviations between the measured and simulated water contents in the peatgro medium were larger over depth than over lateral distance. In contrast, the model criteria matched well for the sandy clay loam and provided MAE of 0.01 to 0.02 m3 m-3 and RMSE of 0.01 to 0.03 m3 m-3, indicating good agreement between the measured and simulated water contents.